Effectiveness Of Act Number 23 Of 2004 Regarding Elimination Of Violence In Household (PKDRT) Against Psychological Violence In Semarang - Moh. Abd Basith; Anis Mashdurohatun (Jurnal Daulat Hukum, 2019)
Every family dreams to build family harmony, happy and loved each other, but in fact many families are feeling uncomfortable, depressed and sad because of violence in the family, whether the violence is physical, psychological, sexual, or neglect.Purpose of the effectiveness of the implementation of Act Number 23 of 2004 on the Elimination of Domestic Violence against psychological violence in the city of Semarang, namely: to determine the effectiveness of the implementation of Act Number 23, 2004. The method used Soerjono Soekanto said that the effectiveness of the implementation of the law in a society is determined by several factors, namely (1) the rule of law, (2) law enforcement officials, (3) legal facilities, (4) community and (5) culture. The approach I use in this study is a sociological juridical legal approach, ie an approach by examining the secondary data first, followed by conducting research in the field of primary data. The results showed that effect implementation of Act Number 23 of 2004 in reducing psychological violence in the city, namely (1) the perceived inadequate (2) and ineffective. This is evident from the level of psychological domestic violence volatile and without a significant decrease. Suggestions authors hope that the government and relevant institutions more concerned about PKDRT and routinely provide information, education and prevention of domestic violence.Keywords: Effectiveness; Psychological Violence; Domestic.